Lending Conditions and Marketing Strategies Of Financial Institutions in Kosovo to Support Access to Finance for Women Entrepreneurs - Ajtene Avdullahi; Vjosa Fejza Ademi (LPPM of NAROTAMA UNIVERSITY, 2020)
Purpose: The main purpose of this paper is to investigate the effort of financial institutions that support female entrepreneurship in a developing economy as well as the marketing strategies that those financial institutions utilize to increase the awareness of the female entrepreneurs concerning their preferential lending conditions and terms. Design/methodology/approach: For our research purpose the secondary data are used such as research papers, books and reports. The comparative method is used to compare the financial institutions lending conditions as well as the marketing and promotional strategies of those institutions. Findings: Access to finance presents one of the main barriers for female entrepreneurs in developing countries. Our results indicate that not so many financial institutions are constantly offering preferential lending conditions and terms for female-owned enterprises. Practical implications: We propose that financial institutions need to increase the number of loans and credit packages that support women's entrepreneurship and to create and promote much more marketing plans and strategies for women financial support packages from banks, to raise awareness of women entrepreneurs regarding the preferential lending conditions and special offers. Paper type: Research paper